Appropriate expression of P57kip2 drives trophoblast fusion via cell cycle arrest. Issue 6 (5th May 2021) - Song, Hong-Lan; Liu, Tai-Hang; Wang, Yong-Heng; Li, Fang-Fang; Ruan, Ling-Ling; Adu-Gyamfi, Enoch Appiah; Hu, Si-Chen; Chen, Xue-Mei; Ding, Yu-Bin; Fu, Li-Juan
Abstract : The syncytiotrophoblast, derived from cytotrophoblast fusion, is responsible for maternal–fetal exchanges, secretion of pregnancy-related hormones, and fetal defense against pathogens. Inadequate cytotrophoblast fusion can lead to pregnancy disorders, such as preeclampsia and fetal growth restriction. However, little is known about the mechanism of cytotrophoblast fusion in both physiological and pathological pregnancy conditions. In this study, P57 kip2 (P57), a cell cycle-dependent kinase inhibitor that negatively regulates the cell cycle, was found to be up-regulated during the process of syncytialization in both primary trophoblast cells and BeWo cells. Co-immunofluorescence with proliferation markers Ki67 and Cyclin-CDK factors further showed that P57 specifically localizes in the post-mitotic cytotrophoblast subtype of the early pregnancy villi. Overexpression of P57 promoted trophoblast syncytialization by arresting the cell cycle at the G1/G0 phase and inhibiting proliferation. Blocking of the cell cycle through a serum starvation culture resulted in an enhancement of cytotrophoblast fusion and the up-regulation of P57. In both spontaneous cytotrophoblast fusion and forskolin-induced BeWo cell fusion models, an initial up-regulation of P57 was observed followed by a subsequent down-regulation. These findings indicate that proper expression of P57 at cytotrophoblast differentiation nodes plays an important role in trophoblast syncytialization.